The leader you want to be : five essential principles for bringing out your best self--every day - Su, Amy Jen (Boston, Massachusetts : Harvard Business Review Press, 2019)
"You can be the leader you want to be--today and every day. Do you find yourself wishing you had more hours in the day? Do you want to do more, yet feel you just can't add another thing to your plate without being overwhelmed by stress or compromising your health, relationships, and integrity? No doubt, as a leader, there are some days when you feel the flow. You're able to make a difference and achieve big goals. You feel confident and energized. On days like this, you're your best self--the leader you want to be. But on other days, you go down a different, negative path, with pressures and doubts making you feel like a lesser version of yourself. How can you be the leader you want to be, every day? The answer is more than a time-management system or a silver-bullet solution for changing your routines. Leadership expert and coach Amy Jen Su's powerful new book helps readers discover that the answer lies within. By focusing in specific ways on five key leadership elements--Purpose, Process, People, Presence, and Peace--you can increase your time, capacity, energy, and ultimately your impact, with less stress and more equanimity. Drawing on rich and instructive stories of clients, leaders, artists, and athletes, as well as on research by experts, the author brings together the best of both Western management thinking and Eastern philosophy to provide a holistic yet hands-on approach. The Leader You Want to Be is the indispensable guide to helping you tap into and expand your leadership capacity so that you can sustain your optimal level of performance and thrive as a leader"--
Introduction: A tale of two leaders : which will you be? -- What gets in the way : the pitfalls of doing -- The power of purpose : reset your compass -- The power of process : reboot your personal operating system -- The power of people : raise your game, raise the game of others -- The power of presence : don't scratch the itch -- The power of peace : loosen your grip -- Pay it forward : create Leader A teams and organizations -- Leader A toolkit -- Leader A master checklist tool -- Leader A assessment -- Leader A onboarding worksheet tool -- managing overwork or stress worksheet tool -- increasing effectiveness, discipline, collaboration, or statisfaction tool.
Includes index.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 05, 2019).
Master record variable field(s) change: 050
Keywords: Leadership; Executive ability; Philosophy, Asian; Executive ability; Leadership; Philosophy, Asian; elektronické knihy; electronic books